(untitled) (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACT AIM- The aim of the present investigation is to study the anti-inflammatory and anti-arthritic activity of different fractions. MATERIAL & METHODS- For the fractionization, dried 50 g ethanolic extracts of Alstonia scholaris extracts were taken and dissolved into distilled water. The water extract was filtered to remove all insoluble components. The water extracts was taken into separating funnel and fractionated with petroleum ether, chloroform and finally with butanol,